Ціннісні виміри трансформації сучасного українського суспільства - Матета, О. А.; Mateta, О. А.; ORCID: https://orcid.org/0000-0002-3087-9832 (Харківський національний педагогічний університет імені Г.С. Сковороди. — Харків, 2018. — Вип. 1 (15). — С. 87-99., 2018)
У статі розглянуто проблеми трансформації українського суспільства. Визначено ціннісні пріоритети громадян України, що виступають важливими індикаторами їхнього сприйняття, відчуття і тлумачення трансформаційних процесів суспільства. Розуміння ціннісної ієрархії українців дозволило нам охарактеризувати стан українського суспільства, його перспективи розвитку, можливості переходу до демократичного транзиту. Встановлено першочергові завдання влади для подолання кризи ідентичності, відродження демократичних цінностей для консолідації українського суспільства. The article deals with the problems of Ukrainian society's transformation. Using the data of sociological surveys that are regularly done by the scientists of the Sociology Institute, the citizens value priorities of Ukraine are identified, which are important indicators of their perception, sensations and interpretation of the society transformation processes. People are disappointed in the changes, growing non-confidence to the institutions of power, lack of desire to participate in political processes. It is concluded that the causes of these problems are, on the one hand, the behavior of the authorities, which lacks democratic traditions, adapts the law to their needs, and uses state institutions for their own enrichment. On the other hand, low political and legal culture of citizens, blurring of public values, domination security values over the freedom values and self-realization. To solve the above problems, the priorities of the authorities are determined: – directing political activities to transform a person into a member of the political community, with a main focus on the rights and freedoms of the individual, its civic duty and emotional-sensory conviction in democratic values, readiness for lawful behavior; – return of trust to state institutions; – revival of national traditions, historical and spiritual values of Ukraine, created by the work of previous generations for the consolidation of Ukrainian society. В статье рассмотрены проблемы трансформации украинского общества. Определены ценностные приоритеты граждан Украины, выступающих важными индикаторами их восприятия, ощущения и толкование трансформационных процессов общества. Понимание ценностной иерархии украинцев позволило нам охарактеризовать состояние украинского общества, его перспективы развития, возможности перехода к демократическому транзиту. Установлены первоочередные задачи власти по преодолению кризиса идентичности, возрождения демократических ценностей для консолидации украинского общества.
Ценностные измерения трансформации современного украинского общества
Axiological transformation measurements of modern ukrainian society
Матета О.А. Ціннісні виміри трансформації сучасного українського суспільства [Електронний ресурс] / О.А. Матета // Сучасне суспільство: політичні науки, соціологічні науки, культурологічні науки: Збірник наукових праць / Харківський національний педагогічний університет імені Г. С. Сковороди. — Харків, 2018. — Вип. 1 (15). — С. 87-99. - Режим доступу: http://journals.hnpu.edu.ua/index.php/politology/article/view/862
Keywords: Політичні науки. Рolitical science. Политические науки; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; цінності; трансформація; ідентичність; політична культура; демократичний транзит; ценности; трансформация; идентичность; политическая культура; демократический транзит; values; transformation; identity; political culture; democratic transit